Edge Domination in Some Path and Cycle Related Graphs. (13th March 2014) - Vaidya, S. K.; Pandit, R. M.
Abstract : For a graph G = V, E, a subset F of E is called an edge dominating set of G if every edge not in F is adjacent to some edge in F . The edge domination number γ ′ G of G is the minimum cardinality taken over all edge dominating sets of G . Here, we determine the edge domination number for shadow graphs, middle graphs, and total graphs of paths and cycles.